Evaluation of the Implementation of the Sekolah Penggerak Program Using the CIPP Model in Middle Schools in East Manggarai Regency - Marianus Tapung; Marselus Ruben Payong; Alfonsus Sam (Green Publisher Indonesia, 2024)
This study is an evaluation of the implementation of the School Mover program in 23 junior high schools in East Manggarai Regency using the Context, Input, Process, and Product (CIPP) model. This study aims to analyze the Context, Input, Process, and Product of the program. The method used in this research is descriptive statistics to measure the perceptions and evaluations of school principals, teachers, school supervisors, facilitators, school committees and stakeholders. The results of statistical measurements of perceptions and evaluations were juxtaposed with data from interviews and document reviews. The results of the data analysis show that the Input, Process and Product aspects fall into the